Integrating gender in agricultural development : learnings from South Pacific contexts - Singh-Peterson, Lila; Carnegie, Michelle (Bingley, U.K. : Emerald Publishing Limited, 2019)
South Pacific island nations are committed to international agreements and regional declarations to progress gender equality within their own territories, yet progress towards Sustainable Development Goal 5, Gender Equality, has been reported as slow and uneven. Tackling persistent gender inequalities in agriculture has been identified as a priority due to the industry's commercial importance to economies and communities across the region, and its role in food security. This book is grounded in the ideology that an alignment between the conceptual and practical understandings of gender equality is a critical component of sustainable development. Two introductory chapters establish the book's broader context. The following chapters draw on six rural case studies from Melanesia (Vanuatu, Fiji and Papua New Guinea) and Polynesia (Samoa and Tonga) across cropping, livestock, horticulture and aquaculture sectors to examine the various ways in which gender has been integrated in agricultural research for development projects. The case study authors explore the opportunities and challenges involved in integrating or mainstreaming gender, from research design to implementation, and reflect on the lessons learned. The final chapters synthesise these shared, field-based learnings and positions them within contemporary gender concepts to contribute to an understanding of how they are translated in practice to diverse South Pacific contexts.
Chapter 1. Introduction: Integrating gender in agricultural development initiatives across the South Pacific: customs, values and intersections / Lila Singh-Peterson and Michelle Carnegie -- Part One -- Chapter 2. Facing the future: backgrounds to agricultural change in the South Pacific / John Connell -- Chapter 3. The international 'gender agenda' in the context of the South Pacific and agricultural livelihoods / Michelle Carnegie and Lila Singh-Peterson -- Part Two -- Chapter 4. Bula coffee: women's access to economic opportunities, the effects on women's agency and their influence on social norms in rural Fijian communities / Marilyn Vilisoni, Ajla Vilogorac and Samira Saif -- Chapter 5. An exploratory approach to understanding women's contributions to the aquaculture sector in samoa: the influence of traditional systems and cultural norms / Joanne Kunatuba, Ana Laqeretabua and Ulusapeti Tiitii -- Chapter 6. Upward reflections on top-down gendered institutions: a community development case study from Tonga / Lila Singh-Peterson, Tema Moala and Louna Sione Hamani -- Chapter 7. Agroecology and sustainable livelihoods as a framework to empower rural Ni Vanuatu women / Cherise Addinsall, Norah Rihai and Antoinette Nasse -- Chapter 8. Community livelihood improvement in the Papua New Guinea LNG project / R. Michael Bourke, Shirley Tombenna, Owen Hughes, Matthew'wela B. Kanua, Agnes Siune and Barbara Pamphilon -- Chapter 9. Research and learning from the 'inside out': processes, practices and pedagogy of a women's agricultural economic empowerment project in Papua New Guinea / Barbara Pamphilon, Veronica Bue and Fredah Wantum -- Part Three -- Chapter 10. Reflections from the South Pacific: navigating intersectionality and customary contexts to progress gender equality and gender equity / Lila Singh-Peterson, Michelle Carnegie, Veronica Bue, R. Michael Burke, Joanne Kunataba, Ana Laqeretabua, Temaleti Moala, and Barbara Pamphilon and Marilyn Vilisoni -- Chapter 11. Conclusion: South Pacific contexts for gender equality scholarship and practice / Lila Singh-Peterson -- Index.
Includes index.
Print version record.
Keywords: Women in agriculture -- Oceania; Women agricultural laborers -- Oceania; Technology & Engineering -- Agriculture -- General; Agricultural science